Analisis Pengendalian Kualitas untuk Meminimalisir Kecacatan pada Produk Telur Menggunakan Metode Statistical Quality Control (SQC) dan Failure Mode and Effect Analysis (FMEA) - Muhammad Firdaus Fadhlullah; Silvia Firda Utami; Ismi Mashabai; Ulfaturrahmi Ulfaturrahmi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Fadhilah Jaya Samawa Farm is a medium-scale laying hen farm located in Sumbawa Regency, West Nusa Tenggara. The main problem is a continuously increasing defect rate, from 4.7% in November 2025 to 10.4% in April 2026, with an average of 5.5% from 443,424 total eggs. This study aims to describe the egg production process, analyze product defects using Statistical Quality Control (SQC), and develop improvement recommendations based on Failure Mode and Effect Analysis (FMEA). SQC was applied through five tools check sheet, histogram, Pareto diagram, p-chart control chart, and cause-and-effect diagram. Results show cracked eggs (35.7%) and thin-shelled eggs (34.2%) as the dominant defects. FMEA analysis identified three highest RPN values from method factors: insufficient floor slope in the cage, non-simultaneous flock replacement per period, and egg collection conducted only once per day. Recommended improvements include correcting cage floor slope, developing a flock replacement SOP, and increasing egg collection frequency.